Dosa Suap dalam Ulangan 16:19 dan Implikasinya terhadap Etika Kepemimpinan di Era Modern - Mayopu, Yusup Amasia; Simanjuntak, Yosua Marsorin (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2025)
The sin of bribery as mentioned in Deuteronomy 16:19 and its implications for ethical leadership in the modern era. The verse emphasizes the prohibition against bribery that can pervert justice, blind the eyes of the wise, and damage the integrity of leaders. In the context of modern leadership, the practice of bribery is still a challenge that threatens morality and justice in various sectors, including government, business, and religious organizations. This study uses a qualitative approach with biblical hermeneutics methods and leadership ethics analysis. The results of the study indicate that the principle of justice in Deuteronomy 16:19 remains relevant and can be a basis for leaders to reject all forms of corruption and nepotism. Leadership based on integrity, transparency, and moral responsibility is the key to creating a just system that is oriented towards the common good. By understanding the implications of the sin of bribery from a biblical perspective, this study confirms that ethical leadership based on biblical values ​​can be a solution in facing moral challenges in the modern era.